Prevalence of thyroid dysfunctions in infants and children with Down Syndrome (DS) and the effect of thyroxine treatment on linear growth and weight gain in treated subjects versus DS subjects with normal thyroid function: a controlled study - AlAaraj, Nada; Soliman, Ashraf T; Itani, Maya; Khalil, Ahmed; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2019)
Background: Individuals with Down syndrome (DS) are at an increased risk of developing thyroid disease, primarily autoimmune, with a lifetime prevalence ranging from 13% to 63%. Unfortunately, there are few studies systematically examining the frequency of thyroid disease in very young children. Aim of the study: The aim of the present study was to investigate the prevalence of different thyroid dysfunctions (TD) in a cohort of infants and children with DS and the growth parameters in subjects with normal versus abnormal thyroid function, followed for 3 years. Patients and methods: All children (n = 102; 48 males and 54 females, aged 2.3±3 years) with the diagnosis of DS who were seen at the General Pediatric Clinic of Hamad General Hospital in Doha (Qatar) from 2014 to 2018 were enrolled in our study. We recorded thyroid function and linear growth parameters [BMI, length/height SDS (Ht-SDS) and weight gain/day] and divided them into 3 groups according to their thyroid function. Group 1: (n = 36 subjects) with normal free T4 (FT4) and TSH; Group 2 (n = 44 subjects) with high TSH >5 and 12 mIU/L and/or FT4 5 mIU/L), especially in those with TSH >12 mIU/L.